Tepung Bekicot sebagai Sumber Protein Pengganti Tepung Ikan dalam Ransum Ayam Pedaging (ACHATINA Sp. MEAL COMPETITIVE WITH FISH MEAL AS PROTEIN RESOURCES FEED OF BROILERS) - Jehemat, Antonius; Indah Koni, Theresia Nur (Jurnal Veteriner, 2013)
A research was conducted on the performance of broilers fed with diet supplemented with Achatina sp.meal as protein substitute of fish meal.  The aim was to increase the use of  Achatina spp. in diet byevaluating the feed consumption, the average daily gain (ADG), the feed conversion, and the dry matterand crude protein digestibility of 120 experiment broilers. The experimental design used was completelyrandomized design (CRD) consisting of five level of Achatina spp. concentration as  substitution of fishmeal.  The levels were: 0% as control, 10%, 20%, 30% 40%, and 50% of Achatina spp meal substitute for fishmeal. The result showed that substitution fish meal by Achatina spp. meal was able to increase significantly(P<0.01) of feed consumption and ADG, but it has no significant (P<0.05)  effect on feed conversion, and drymatter and crude protein digestibility. It was concluded that Achatina spp. meal can be used in diet as asubstitute for fish meal up to 30%, with ADG about 25.71 g (highest level).
Keywords: Broiler, Achatina spp. meal, Fish meal, Digestible, and daily gain